Clinical and Pathogenetic Aspects of Combined Hepatitis "B" And "C" (Eurasian Medical Research Periodical, 2023)
In order to study the issues of pathogenesis, clinic and diagnosis of combined liver lesions with hepatitis B and C viruses, 38 patients with various forms of mixed hepatitis B + C were comprehensively examined. During the infectious process of combined HBV/HCV etiology, indirect signs of mutual inhibition of two hepatotropic viruses were observed. The severity of clinical, laboratory and histological changes in the liver in latent forms is mainly due to HCV infection; it is characterized by the rapidity of HBeAg/HBeAb seroconversion and the disappearance of HBV DNA from the patient's blood against the background of ongoing HCV persistence. Isolation of various variants of the course of mixed hepatitis is uninformative in relation to the outcome and prognosis of the disease. At the same time, a thorough assessment of the activity of viral replication of both pathogens determines the choice of rational therapy.